MR Imaging of Mushroom-like Skin Adnexal Tumors in the Scalp: A Report of Two Cases - Arai, Manabu (Magn Reson Med Sci, 2019)
Few studies had been published regarding imaging findings of skin adnexal tumors. We experienced two giant cases of them with a characteristic mushroom-like growth pattern. MRI showed a circumscribed mushroom-like shaped mass extruding from the subcutaneous tissue with microcystic lesions. Although differentiation between benignancy and malignancy may be difficult by radiological examinations, MRI may be helpful to identify its origin and differentiate soft tissue tumors with skin adnexal tumors in having these imaging findings.